5E Learning Cycle in Practicing Written and Oral Argumentation Skills - Valensa Yossyana; Nadi Suprapto; Tjipto Prastowo (IJORER : International Journal of Recent Educational Research, 2020)
The argumentation ability plays an important role in the support of life skills required in the 21st century, but it has been recently found that this ability among students remains at a low level. This situation has asked for intervention to make the necessary skills improved. Thus, this study aims to examine students’ argumentation skills in written and oral senses by implementing the 5E Learning Cycle in a classroom setting and to analyze the effects of the implementation on ability the skills. The design of this study was pre-experimental research using one group pretest-posttest method. The learning materials used during the study were syllabus, lesson plans, handouts, worksheets, and exercises. Meanwhile, the ability of scientific argumentation skills was evaluated and assessed using pretest-posttest given and interviews in the form of descriptive questions and the corresponding guidelines. The results of the study are here reported as three separate findings. Firstly, the application of the 5E Learning Cycle in science learning allowed the students to practice their scientific argumentation skills. Secondly, direct observations found that most activities were well performed during classroom learning. Thirdly, group discussions in the 5E Learning Cycle have a good contribution to the students' scientific argumentation skills.